2008
DOI: 10.1177/0269881108092120
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids (fish-oil) and depression-related cognition in healthy volunteers

Abstract: Omega-3 polyunsaturated fatty acid (n-3 PUFA) supplementation may be beneficial in the treatment of several psychiatric disorders, including depression. A small number of studies have suggested that there may also be cognitive and mood effects in healthy samples. The purpose of the present study was to investigate the effects of n-3 PUFA on depressionrelevant cognitive functioning in healthy individuals. Fifty-four healthy university students were randomized to receive either n-3 PUFA supplements or placebo fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 42 publications
(55 reference statements)
4
84
5
Order By: Relevance
“…0.8 g/day in Fontani et al (2005a) compared to 0.25 g/day in Antypa et al (2009) and 0.24 g/day in Karr et al (2012)). Subsequent research has compared DHA-rich fish oil to EPA-rich fish oil to better understand whether the DHA or EPA content moderates differences in cognitive performance.…”
Section: Young Adultsmentioning
confidence: 81%
See 1 more Smart Citation
“…0.8 g/day in Fontani et al (2005a) compared to 0.25 g/day in Antypa et al (2009) and 0.24 g/day in Karr et al (2012)). Subsequent research has compared DHA-rich fish oil to EPA-rich fish oil to better understand whether the DHA or EPA content moderates differences in cognitive performance.…”
Section: Young Adultsmentioning
confidence: 81%
“…Further, fish oil did not influence cognitive performance across a range of tasks measuring response inhibition, facial expression recognition, and memory. Fish oil did increase risk-seeking decision-making in gains only trials of a gambling task as well as reaction time in both gains-only and losses-only trials relative to placebo, together suggesting that omega-3 PUFA supplementation increased willingness to make calculated risks rather than increased impulsiveness (Antypa et al, 2009). However, the risk-based decision-making task was only administered after supplementation, making it impossible to determine whether fish oil and olive oil differentially changed risk taking pre-to post-supplementation.…”
Section: Young Adultsmentioning
confidence: 95%
“…They found increased feelings of vigor and reduced feelings of anger, anxiety, fear, depression, and confusion in the n-3 PUFA group compared to placebo (Fontani et al, 2005a,b). However, a more recent study found that 2.3 g/day n-3 PUFA (approximately 7:1 EPA:DHA) reduced feelings of POMS fatigue only (Antypa et al, 2009).…”
Section: N-3 Pufas and Mood And Cognitionmentioning
confidence: 92%
“…Omega-3 fatty acid supplementations containing EPA and DHA in varying amounts have been reported to improve visual attention and information processing speed in some (Fontani et al 2005(Fontani et al , 2009) but not all (Antypa et al 2009;Jackson et al 2012) studies. De Groot et al (2007) found higher levels of AA were associated with a faster learning curve on the Stroop task measuring general speed of information processing; however, the opposite was found with DHA.…”
Section: Fatty Acidsmentioning
confidence: 99%